STRATEGI PEMASARAN PRODUK PEMBIAYAAN KEPEMILIKAN EMAS di BANK SYARIAH INDONESIA - Harahap, Ferda Yani; Putra, Purnama (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2023)
This study aims to determine and analyze the marketing strategy of gold ownership financing products at BSI KC Bekasi Summarecon. The approach used in this study is a descriptive qualitative approach. In addition to being analyzed qualitatively descriptively, the author uses SWOT analysis with IFAS and EFAS matrices. The study's results using the SWOT analysis method from internal and external factors showed that BSI KC Bekasi Summarecon was included in quadrant I. From the analysis results obtained an aggressive strategy, this strategy indicates that the company's condition is vital and can continue to grow by seizing existing opportunities to achieve maximum profit. This position in quadrant I is very profitable and can be marketed optimally by implementing a marketing mix policy that supports an aggressive strategy of gold ownership financing products.